Study of Salivary Uric Acid and serum Uric acid And Their Correlation with Maternal Outcome in Pre- Eclampsia - Madaan, Sparsh; Jaiswal, Arpita (International Journal of Psychosocial Rehabilitation, 2020)
In present time, there is need of validation of non invasive tests. So the study is planned to establish relation between uric acid of saliva and uric acid of serum in women with singleton pregnancy with preeclampsia.To determine levels of salivary uric acid in pre-eclampsia.To determine levels of uric acid of serum in pre-eclampsia.To determine correlation of uric acid of serum and uric acid of saliva with maternal outcome in pre-eclampsia.Unstimulated whole expectorated saliva from each pregnant woman will be collected into sterile tubes 8-9am after rinsing of mouth with 5 ml of distilled water to wash out exfoliated cells. 2 ml venous blood sample will be collected at the same time from the subject to measure uric acid of serum levels. Samples will be centrifuge them and supernatant will be used for analysis of uric acid. Estimation of salivary and uric acid of serum will be done by colorimetric method on automated clinical chemistry analyzer.There exists positive correlation between uric acid of serum levels and adverse maternal outcome.As saliva collection is easy, non-invasive, costeffective requiring simple instruction for collection. So uric acid of saliva testing is a useful approach for monitoring pre-eclampsia at community and hospital setting.